THE EFFECT OF THE APLICATION OF THE COOPERATIVE LEARNING MODEL TYPE THE POWER OF TWO ON THE SCIENCE COMPETENCE OF CLASS VII JUNIOR HIGH SCHOOL STUDENTS - Nova Desrian Siska; Lufri Lufri (Department of Science Education, 2022)
This research aims to determine the effect of the application of the cooperative learning model type The Power of Two on global warming material on the cognitive competence of class VII students of SMPN 1 South Solok. This research was a Quasi Experiment type with a randomized control group posttest only design. In taking the sample used cluster random sampling. And the science learning achievement test sheet is an instrument in this study. In this study, the t test was used as a tool in analyzing the test results at a significant level of 0.05. Thus obtained tcount 3.80> t table 1.68. This proves that the hypothesis is accepted, namely that there is a positive effect of the application of the cooperative learning model type The Power of Two on the cognitive competence of class VII students of SMPN 1 South Solok. Based on this, it can be concluded that the use of cooperative learning model The Power of Two type on cognitive competence in science lessons shows a positive impact.